Chronic Myeloid Leukemia and Chronic Lymphocytic Leukemia: A Case Report on Rare Co-occurrence of both Conditions Simultaneously - Kumar, Amrat; Meena, FNU; Idrees, Muhammad; Patel, Anush (Archives of Clinical and Biomedical Research, 2024)
Chronic lymphocytic leukemia (CLL) and chronic myeloid leukemia (CML) are two of the most common hematological malignancies among elderly individuals. While CLL is characterized by mature lymphocyte proliferation, CML is a myeloproliferative disease induced by the BCRABL gene. Coexistence of these two diseases is rare and can occur either sequentially or concurrently. In this case report, we describe a 74-year-old male patient with a medical history significant for multiple comorbidities, including prostate cancer, who presented with leukocytosis and found to have monoclonal B-cell lymphocytosis, a precursor to CLL on peripheral blood flowcytometry. Over time, the patient continued to have persistent lymphocytosis and developed basophilia, so repeat workup was done with flowcytometry and BCR/ABL1 on which he was diagnosed with both CLL and CML simultaneously. The patient was started on imatinib, which led to a major molecular response with significant improvement in leukocytosis and is being monitored for CLL. Our case report contributes to the limited literature on the simultaneous occurrence of CML and CLL and emphasizes the importance of considering the possibility of coexisting CML and CLL in patients presenting with features of both diseases.